Efecto de herbicidas post-emergentes en el rendimiento del cultivo de arroz (oryza sativa), irrigado al trasplante en Tarapoto - Sánchez Romero, Jovany (2001)
The aim of the study was to evaluate et degree of phytotoxicity to the crop and weed control efficacy of four post-emergent herbicides and / or mixed in rice (Oryza sativa) Capirona variety and determine the benefit-cost ratio. The land on which the research was developed is the farm called "The Core", located 8 km. The city of Tarapoto, - Department of San Martin. The statistical analysis used was the completely randomized design, with six treatments and four replicates per treatment blocks. Treatment (control without weeding) T5 obtained higher yield of fresh and dry matter of weeds with average 2 095.83 and 628. 75 Kg I was without any weed control. Sodium Benzoate dose and 0.4 L I Witness has obtained with weeding paddy rice yields averaging 7 924.30 and 7624.80 kg I ha. Sodium benzoate dose of 0.4 L / ha. He earned less phytotoxicity with average grade 2.0 and 0.0 phytotoxicity at 4 and 8 days. Cost analysis -Benefit treatment (Sodium Benzoate) T1 is reporting higher net profit of S /. 1440.60 nuevos soles with a yield of 7924.30 kg / ha and cost-benefit ratio of 69.70%